In hunt for size: Merger formation in the oil industry - Leslie Neubecker; Manfred Stadler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2003)
This paper analyzes the recent mergers in the oil industry. Oil is assumed to be a homogeneous good which is produced by a small number of firms with different unit costs. Merger formation is endogenously explained as a result of cooperative decisions. We show that the mergers are amongst very asymmetric firms if initial size differences are moderate. If size differences are large, however, the more efficient firms participate in the mergers, while the least efficient firms are not attractive partners and, therefore, remain independent in the post-merger market.
urn:nbn:de:bsz:21-opus-18732
Keywords: C71; G34; L71; 330; Asymmetric horizontal mergers; Coalition formation; Oil industry